Effect of roadside trees on pedestrians’ psychological evaluation of traffic noise - Nguyen, Thulan; Morinaga, Makoto (Frontiers in Psychology, 2023)
Introduction This study aims to investigate the interplay between roadside trees and pedestrians’ assessment of traffic noise and comfort. The study examines the potential effects of visual and design elements of roadside trees on the overall soundscape comfort. Methods The study design involves a systematic exploration of different conditions, encompassing traffic volume, distance from sound source, and tree density. For each combination, two experimental scenarios are created: (1) participants experience a binaural sound recording exclusively, and (2) participants experience the same binaural recording while concurrently immersed in a virtual reality (VR) video. Results Analysis of participants’ noise perception, measured using a quiet-noisy scale, reveals no significant disparity between conditions. This suggests that the mere presence of roadside trees does not necessarily lead to a perceived reduction in noise loudness. However, evaluation of sound intensity exposes a notable discrepancy between low and medium tree density levels. Furthermore, the study confirms the impact of roadside tree visibility, with scenes containing trees yielding more positive evaluations compared to sound-only scenarios. Remarkably, the absence of trees in the roadside scene garners consistent evaluations across both experimental conditions. Significantly, higher roadside tree density in conjunction with the combined sound and VR video condition prompts a more favorable assessment than the sound-only scenario. Discussion While the study indicates that roadside trees might not substantially mitigate perceived physical noise levels, their influence on the psychological well-being of urban inhabitants is considerable. The findings highlight that even though these trees may not overtly diminish noise, they hold substantial potential to enhance the overall comfort and well-being of city residents. This underscores the multifaceted benefits of integrating green spaces into urban design for improving the quality of urban soundscapes and residents’ experiences.